WAYS OF IMPROVING THE INTERACTION BETWEEN LOCAL STATE ADMINISTRATIONS AND LOCAL GOVERNMENT BODIES UNDER THE CONDITIONS OF MARITAL STATE (Bulletin of criminological association of Ukraine, 2024)
A normative-legal direction for improving the interaction of local state administrations and local self-government bodies under martial law has been identified, within the framework of which it is considered necessary to harmonize the provisions of the Law of Ukraine "On the Legal Regime of Martial Law" and the Laws of Ukraine "On Local State Administrations" and "On Local Self-Government in Ukraine". Attention was focused on the need to create appropriate conditions for legal support of the activities of regional state administrations and local self-government bodies. Attention is focused on the fact that the coordination of interaction between local self-government bodies and local state administrations is critically important, especially in the conditions of martial law. It was established that within the framework of the personnel direction of improving the interaction of local state administrations and local self-government bodies in the conditions of martial law, it is necessary to: a) simplify the bureaucratic procedures for employment of employees of military administrations of settlements, in particular, former employees of local government; b) conducting joint trainings and exercises for employees of local state administrations and representatives of local self-government bodies in order to increase their readiness to act in martial law conditions and provide them with the necessary knowledge and skills; c) providing local state administrations and local self-government bodies with the necessary material, financial and human resources for the effective performance of their duties during martial law.
Keywords: improvement; interaction; martial law; local state administrations; local self-government bodies